Construction waste governance in China: policy analysis and roadmap for circular economy transition - Li, Kaiyi; Wang, Kun; Salleh, Hafez Bin; Chen, Yaying (Journal of Civil Engineering and Management, 2026)
Despite the proliferation of circular economy (CE) policies targeting construction and demolition waste – the largest urban solid waste stream in China – a critical policy-practice gap persists between regulatory frameworks and on-site recycling practices. Existing literature often lacks a systematic diagnosis of the institutional and behavioral barriers hindering this sector’s transition to circularity. Drawing on policy design theory, this study formulates an integrated analytical framework that synthesizes policy instrument analysis with stakeholder-centered perspectives to address this research gap. By integrating a mixed-methods content analysis of 925 policy documents with qualitative insights from 23 expert interviews, this study identifies six systemic deficiencies in China’s CE transition in the construction sector: institutional fragmentation, policy instrument imbalance, limited upstream stakeholder engagement, regional disparities, insufficient standardization, and inadequate economic incentives. To transcend these barriers, the study then proposes a novel dynamic transformation roadmap. Unlike static solutions, this framework articulates a phased evolution (short-, medium-, and long-term) that guides the transition from rigid administrative control to a market-driven, lifecycle-integrated ecosystem.